Chronological improvement in precision oncology implementation in Japan. Issue 11 (2nd September 2022) - Sunami, Kuniko; Naito, Yoichi; Komine, Keigo; Amano, Toraji; Ennishi, Daisuke; Imai, Mitsuho; Kage, Hidenori; Kanai, Masashi; Kenmotsu, Hirotsugu; Koyama, Takafumi; Maeda, Takahiro; Morita, Sachi; et al.
Abstract: In Japan, comprehensive genomic profiling (CGP) tests for refractory cancer patients have been approved since June 2019, under the requirement that all cases undergoing CGP tests are annotated by the molecular tumor board (MTB) at each government‐designated hospital. To investigate improvement in precision oncology, we evaluated and compared the proportion of cases receiving matched treatments according to CGP results and those recommended to receive genetic counseling at all core hospitals between the first period (11 hospitals, June 2019 to January 2020) and second period (12 hospitals, February 2020 to January 2021). A total of 754 and 2294 cases underwent CGP tests at core hospitals in the first and second periods, respectively; 28 (3.7%) and 176 (7.7%) patients received matched treatments ( p  < 0.001). Additionally, 25 (3.3%) and 237 (10.3%) cases were recommended to receive genetic counseling in the first and second periods, respectively ( p  < 0.001). The proportion was associated with the type of CGP test: tumor‐only ( N  = 2391) vs. tumor‐normal paired ( N  = 657) analysis (10.0% vs. 3.5%). These results suggest that recommendations regarding available clinical trials in networked MTBs might contribute to increasing the numbers of matched treatments, and that tumor‐normal paired rather than tumor‐only tests can increase the efficiency of patient referrals for genetic counseling. Abstract : We investigated the improvement in precision oncology by evaluating and comparing the proportion of patients receiving genomically‐matched therapies and referred to genetic counseling among all designated core hospitals between two study periods (First period: 11 hospitals, June 2019 to January 2020; Second period: 12 hospitals, February 2020 to January 2021). Our results revealed that both the proportion of matched therapies and referrals to genetic counseling improved chronologically, from 3.7% to 7.7% (p 0.001) and 3.3% to 10.3% (p 0.001), respectively.